The role of neighborhood on preterm birth among a high-risk group of birthing people in Boston, MA - Yarden S. Fraiman; Serena A. Rusk; Janet Rich-Edwards; Xiaboin Wang; Jonathan S. Litt (BMC, 2024)
Abstract Background Preterm birth (PTB) is associated with adverse short- and long-term health. There are known racial, ethnic, and socioeconomic inequities in PTB. Because of historical de jure and modern-day de facto segregation and neighborhood divestment, neighborhoods are a source of structural racism and disenfranchisement and a potential target for policies and interventions to reduce PTB inequity. However, the role of neighborhoods on PTB, specifically among high-risk birthing people, is largely unexplored. Methods The Boston Birth Cohort is a longitudinal birth cohort of birthing people-infant dyads at a safety-net hospital in Boston, MA between 2000 and 2018. The primary outcome was preterm birth at 35 weeks or prior. The primary predictor was neighborhood defined by census tract. We used generalized linear mixed effects models to test our hypothesis that neighborhood accounts for a signficiant proportion of PTB risk among socially at-risk birthing people. Results In multilevel models, neighborhoods were a significant predictor of preterm birth, yet accounted for only 3% of the variability in outcome. In models stratified by race, individual-level factors such as prior preterm birth, nativity status, and advanced birthing person age were significant predictors of PTB. Conclusions Neighborhood is a significant, though small, predictor of preterm birth in a high-risk birthing population. These findings suggest that individual-level interventions, rather than neighborhood-level policies, may be more effective in reducing preterm birth among high-risk birthing populations.